Desenvolvimento e validação de modelos de medição da densidade corporal de um grupo de universitários - Cursino, Carlos Magno Padilha (2009)
Estimating corporeal density and fat in human bodies can be realized by using several laboratory methods: directly, indirectly or double indirect. The direct method is the only one which allows estimating the corporeal fat with such a better precision by means of dissecting the cadaver. In order to get this estimative, one of the most precise indirect method is the one of hydrostatic weight, which is considered the reference one in this study. For estimating the corporeal fat the double indirect method has been used by predicting measure models, which have been developed for populations of different ethnic groups. Many times these models have been employed with no criterion, occasioning errors. In this thesis the corporeal density measuring and fat percentage of 199 undergraduate students were estimated, with 62 female students in the age between 18 and 27 and 137 male students in the age between 18 and 35. Measuring skinfold thickness, height and body mass have been done in the group of undergraduate students. Models for estimating the body density were developed and validated. Thirteen of the models were made for the females and eleven of them were developed for the males. It has been conducted a cross validation of the eleven male measuring models which have been developed in this thesis, as well as of six measuring models which have been developed by other authors. A comparison has been made between the body densities measured by using the standard method and the densities which were estimated by the models.Three models used for the females attended the Heyward & Stolarczyk criterion, as well as the morphology one and the practical one. Through validation they presented a correlation coefficient (R) between 0.802 and 0.835, and an estimating standard error (EPE) between 0.0070 g/cm3 and 0.0075 g/cm3. Four measuring models which have been developed in this study for the male sex, within the cross validation procedure, presented strong correlations between 0.774 and 0.805, and EPE between 0.0065 g/cm3 and 0.0070 g/cm3. These values were classified by Lohman as very good. They attended the Heyward & Stolarczyk criteria, the morphology one and the practical one. No one of the six measuring models which have been developed by other authors was recommended for being used in this sample once they did not attend the validation criteria.